Population dynamics of fruit ﬂies, Bactrocera spp. infesting vegetable crops in Himachal Pradesh, India - Singh, Mohinder; Sharma, P L; Rana, V K; Sharma, Deeksha; Sharma, Priyanka (Indian Journal of Plant Protection, 2017)
Population dynamics of fruit ﬂies infesting vegetable crops was studied from 2011-12 to 2013-14 using cue lure traps at two locations, Nauni (mid hills) and Neri (low hills) representing two different agro-climatic zones of Himachal Pradesh, India. Three fruit ﬂy species viz., Bactrocera cucurbitae (Coquillett), Bactrocera tau (Walker) and Bactrocera scutellaris (Bezzi) were recorded in trap catches. B. scutellaris dominated the trap catches, accounting for 55.0 and 66.7% of the population at Nauni and Neri, respectively, followed by B. tau and B. cucurbitae. There were two peaks in fruit ﬂy populations, frst during summer (May-June), and second in rainy/post rainy season (August- September). The highest population of fruit ﬂies in trap catches was recorded in fourth week of August and fourth week of September at Neri (low hills), and Nauni (mid hills), respectively, while it was lowest during December to February. The species diversity was greater at Nauni (Shannon index of diversity, H-0.9045) than at Neri (H-0.8510), whereas the species dominance was higher at Neri as compared to Nauni. At Nauni, all the three species exhibited signifcant positive association with maximum and minimum temperatures. The trap caches of B. cucurbitae and B. tau also showed signifcant correlation with relative humidity. At Neri, however, all the fruit ﬂy species showed signifcant positive correlation with minimum temperature, relative humidity and rainfall.